Strategi Guru dalam Meningkatkan Motivasi Belajar Siswa Kelas II MI NW Tampih: Teacher Strategies in Improving Student Learning Motivation in Class II MI NW Tampih - Yuliana Susanti (Al-Faiza : Journal of Islamic Education Studies, 2025)
Strategy is a plan that contains a series of activities designed to achieve educational goals. The problem in this study is how a teacher can increase student motivation. The above can be understood first if the learning is delivered in a super serious way. This study aims to determine the teacher's strategy in managing class II MI NW Tampih. The type of research used is qualitative descriptive research, data is obtained by conducting observations, interviews and documentation. The validity of the researcher's data uses triangulation techniques. Data analysis is carried out in four stages, namely: data collection, data reduction, data presentation, and drawing conclusions. The results of this study indicate that how a teacher's strategy in providing student learning motivation in class is an effort made by the teacher to help create optimal conditions. Classroom management is an art or work practice where teachers work individually or through others to optimize class resources for the creation of an effective and efficient learning process, as well as effective methods carried out by a teacher so that the learning process is not boring.